Modelling the sustainable agriculture management adaptation practices: Using adaptive capacity as a mediator - Masud, Muhammad Mehedi; Akhtar, Rulia; Al Mamun, Abdullah; Uddin, Md. Sayed; Siyu, Long; Yang, Qing (Frontiers in Environmental Science, 2022)
The purpose of this research is to investigate the mediating role of farmers’ adaptive capacity between adaptation practices and economic, social, natural, technological, and institutional limitations. A survey questionnaire was employed to collect data, which was subsequently analysed using PLS-Structural Equation Modelling Structural equation modelling. The entire population was stratified into 27 Pertubuhan Peladang Kawasan out of which 500 targeted respondents were randomly selected from seven strata for data collection. The findings revealed that only 67% of farmers are aware of adaptation practices, while 33% are uninformed. The study also revealed that economic, social, natural, technological, and institutional barriers affect farmers’ adaptive capacity levels and ultimately hamper their adaptation practices. This result further affirms the influence of farmers’ adaptive capacity level on their adaptation behaviour. Adaptation strategies are essential to mitigate the negative effects of climate change. However, the success of these strategies is contingent upon the farmers’ adaptive capacity level, which is strained by several barriers. The findings contribute to the development of a national adaptation plan in a bid to aid the implementation of the 2011–2020 National Agri-Food Policy (NAP) to increase the competitiveness and production capacity of the entire agri-food industry value chain and ensure food security in Malaysia. This study will help policymakers come up with a good policy framework to get rid of the problems that get in the way of adapting to climate change.